Analisis Hukum Islam tentang Penerapan Khiyar dalam Transaksi Jual Beli Modern - Khairi, Rifqil; Zakir, Muhammad; Assyifa, Zubaidah; Rahmawati, Rahmawati (Journal of Legal Sustainability, 2025)
This study aims to analyze the application of the concept of khiyar in modern sales transactions, particularly in the context of online trade and digital sales systems that are rapidly evolving today. The concept of khiyar in Islamic law grants both the seller and the buyer the right to proceed with or cancel the contract under certain conditions in order to uphold justice and prevent practices that may harm either party. The research method used is a qualitative approach with a normative juridical analysis, examining Islamic legal sources such as the Qur’an, Hadith, and classical as well as contemporary fiqh muamalah literature, and comparing them with the practices of modern sales transactions, including return policies, warranty systems, and consumer protection mechanisms in e-commerce. The findings indicate that the principle of khiyar has been substantially implemented in various modern transaction features, such as return policies, trial periods, and customer complaint systems. However, its implementation has not fully aligned with the principles of fiqh muamalah due to the presence of elements of uncertainty (gharar) and injustice in several digital trade practices. Therefore, education and regulatory strengthening based on Sharia principles are required to ensure that the application of khiyar rights provides fair protection for both consumers and business actors in accordance with the values of Islamic law.